2023
DOI: 10.1177/00469580221150094
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Needs of HPV-Positive Women

Abstract: HPV is the most prevalent sexually transmitted diseases causing a variety of clinical manifestations ranging from warts to cancer. This study aimed to examine the challenges and needs of HPV-positive women. In this qualitative study, we analyzed data extracted from semi-structured face-to-face interviews with 31 Iranian HPV-positive women using a conventional content analysis approach using MAXQDA.10 software. Data were collected from her at the women’s clinic from 21 January 2022 to her 19 February 2022. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This type of transmission is characterized by HPV-induced lesions, which encompass anogenital and laryngeal areas. Several authors state that intrauterine transmission of HPV has been suspected, leading to laryngeal or oral papillomatosis, and the presence of vulvovaginal secretions in HPV-positive mothers is related to vertical transmission of the virus at the time of delivery (8,9,10). It is crucial to note that the likelihood of infection transmitted from mother to child depends largely on the viral genotypes present in the mother.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This type of transmission is characterized by HPV-induced lesions, which encompass anogenital and laryngeal areas. Several authors state that intrauterine transmission of HPV has been suspected, leading to laryngeal or oral papillomatosis, and the presence of vulvovaginal secretions in HPV-positive mothers is related to vertical transmission of the virus at the time of delivery (8,9,10). It is crucial to note that the likelihood of infection transmitted from mother to child depends largely on the viral genotypes present in the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta, et al (18), conducted a systematic review of the literature that demonstrated a wide variation in the prevalence of HPV in pregnant women, which can be attributed to changes in the hormonal environment and decreased immunity. In addition, in several populations, several types of HPV have been found to be associated with premature rupture of membranes, preeclampsia, fetal growth restriction, preterm birth, and placental abnormalities (9). During pregnancy, the change in the hormonal environment and the immune response may favor the presence and persistence of HPV infection (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women who test positive for HPV often experience significant anxiety and uncertainty due to the associated risk of developing cervical cancer [ 17 ]. This anxiety extends to concerns about the potential effects on pregnancy and childbirth [ 18 ]. Studies involving gastric cancer and hemodialysis patients have demonstrated that uncertainty can influence the intention to engage in preventive behavior, with greater uncertainty correlating with a reduction in health-promoting actions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%